Superman’s Overconfidence In His God Complex As Seen In Superman: Red Son Movie - Bagus Pratama Wijayanto; Kusuma Wijaya; Rommel Utungga Pasopati (Gudang Jurnal Multidisiplin Ilmu, 2025)
This article examines how the Superman: Red Son movie by Sam Liu portrays Superman’s overconfidence. The movie is about another universe in DC Comics where Superman is born in Soviet Union within Cold War. It also shows how Superman is practicing his overconfidence within his God Complex as the sole legitimate ruler for his people in Superman: Red Son. In this movie, Superman is depicted as a very tyrannical Soviet leader. Superman also thinks that he is better than other people. He believes that all that he does is justified and bearing truth according to his own values. Through qualitative method, this article would like to explore more whether Superman’s God Complex is closely related to condition of overconfidence. In analysis, Superman is proved to practice overconfidence in underestimating other people, being superior to others, and being arrogant all the time. In conclusion, it is clear that Superman’s God Complex is in matter of overconfidence, especially in his superior behavior towards other people.